Preservation of semi-liquid Aloe gel: total phenolic and emodin content - Susana I.W Rakhmani; S Sitompul; J Rosida; T Purwadaria; A.P Sinurat (Indonesian Center for Animal Research and Development (ICARD), 2004)
Semi liquid Aloe gel (LBSC) was preserved using sodium chloride (1, 2 and 3%) and sugar (10, 20 and 30%) for 7 weeks at 4ºC. Physical observations (color, odor and gas) and chemical analysis (total phenolic and emodin) were performed every week during preservation. Changing color was observed at the fourth week and until the seventh week. The total phenolic content decreased by 23.2, 12.9 and 19.0% in LBSC with 1, 2 and 3% salt respectively. The total phenolic content in LBSC with 10, 20 and 30% sugar decreased by 64.0, 53.8 and 30.4% respectively. The emodin content decreased by 60.7% for control (LBSC alone), but in LBSC with 1, 2 and 3% salt it was decreased by 26.2, 19.2 and 50.8% respectively. The emodin content in LBSC with 10, 20 and 30% sugar decreased by 70.5, 67.4 dan 82.4% respectively. Emodin was more unstable than total phenolic. Preservation using sugar was not preserve the availability of emodin, while salt could inhibit the decrease of emodin concentration in LBSC. Preservation of LBSC with 2% table salt gave the lowest decrease of emodin and total phenolic contentsKey words: Aloe vera, fenol, emodin, preservation